Preferences for digital versus printed textbooks: Existing and emerging challenges - Levkov, Nikola (AIS - Association for Information Systems, 2022)
The Covid-19 pandemic is seen by many in the world as a “booster dose” for more rapid digitalization in schools and universities. Research in the past mainly reported inconclusive results about students’ preferences for digital textbooks, although there are significant advances in information technology development and the availability of digital textbooks. We think that preferences have many contextual underlying causes, and they cannot be simply detached and measured only through the behavioral choice (print vs. digital textbook) neglecting the broader context. Hence, we propose conducting a thorough systematic literature review (SLR) on studies that investigated the preferences of three key stakeholders’ students, teachers, and parents to better understand the potential contextual circumstances that trigger certain preferences. This short paper forms the first step towards creating a deeper understanding of preferences for digital textbooks as a phenomenon and research area among IS researchers.
Keywords: digital textbook, printed textbook, preferences, students, teachers, parents